Research on cross-cultural adaptation and educational management of international students in China: Case of African students at Zhejiang Normal University - Di, Weifeng; Zhang, Sijia; Lian, Xing; Oubibi, Mohamed; Li, Dana; Ding, Lisi; Zhang, Zhujia; Yang, Tianping (Frontiers in Psychology, 2022)
With the new development of China-Africa relations and the vigorous development of the country's education for international students, the number of African students studying in China has surged, and the difficulty of education management in colleges and universities has increased accordingly. However, many scholars have conducted multi-angle and in-depth research on the educational management model of international students in China, educational management policies for international students in China, current situation and optimization strategies. The research dimension is relatively single and lacks an overall perspective. This study takes the educational management practice of African international students in Zhejiang Normal University as the breakthrough point and introduces the investigation of international students' cross-cultural adaptability. A sample of African students coming to China was selected from Zhejiang Normal University (n=475). This study designed a questionnaire based on the dimensions of enrollment management, teaching management, and daily management combined with the teaching satisfaction, cultural adaptability, and emotional attitude of African international students in China. Using SPSS 26 software to conduct data correlation analysis, the results found problems such as lack of enrollment channels, incomplete enrollment promotion, unreasonable curriculum settings, inadequate implementation of the tutor responsibility system, and excessive differentiated management. The characteristic countermeasures for the education management of African international students in China are to uphold the thinking of a community with a shared future for mankind, optimize the enrollment management of African students in China; advocate the value cognition of "harmony but different", improve teaching management; implement "people-oriented" services Purpose, improve daily management; deepen community value recognition, and promote students' cross-cultural adaptation.